Rinoscopia como ferramenta diagnóstica - estudo retrospectivo de 52 felinos. - Lima, Luiz Ricardo Silva [UNESP] (The Journal of Veterinary Science, 2025)
Nasal disorders in cats are considered a challenge, due to their nonspecific clinical signs and multifactorial aetiology. Rhinoscopy is an important diagnostic tool, as it allows direct visualisation of the nasal cavity and the collection of samples. In this retrospective study, 52 cats undergoing rhinoscopy were evaluated in conjunction with clinical, radiographic, microbiological, and histopathological data. The endoscopic score was determined based on the type of secretion, the degree of turbinate destruction, and mucosal hyperaemia, with each parameter scored from 0 to 3, yielding a maximum score of 9. Although mucopurulent discharge was a frequent finding, no significant association was observed with positive bacterial cultures, suggesting its low specificity as an indicator of active bacterial infection. Histopathology was performed in 30 cases, with the main diagnoses being inflammatory rhinitis (66.7%) and neoplasia (30%), predominantly lymphoma. Fungal rhinitis, attributed mainly to Sporothrix spp., showed high endoscopic scores (6–9) and the presence of fungal colonies. Among the 11 cases in which rhinoscopy suggested the presence of a polyp, histopathological examination confirmed neoplasia in three, reinforcing the importance of this complementary diagnostic procedure. The results reinforce the value of rhinoscopy in the evaluation of the nasal cavity; however, the isolated interpretation of endoscopic findings is insufficient to predict the diagnosis in cats with nasal disorders.

Nasal disorders in cats are considered a challenge, due to their nonspecific clinical signs and multifactorial aetiology. Rhinoscopy is an important diagnostic tool, as it allows direct visualisation of the nasal cavity and the collection of samples. In this retrospective study, 52 cats undergoing rhinoscopy were evaluated in conjunction with clinical, radiographic, microbiological, and histopathological data. The endoscopic score was determined based on the type of secretion, the degree of turbinate destruction, and mucosal hyperaemia, with each parameter scored from 0 to 3, yielding a maximum score of 9. Although mucopurulent discharge was a frequent finding, no significant association was observed with positive bacterial cultures, suggesting its low specificity as an indicator of active bacterial infection. Histopathology was performed in 30 cases, with the main diagnoses being inflammatory rhinitis (66.7%) and neoplasia (30%), predominantly lymphoma. Fungal rhinitis, attributed mainly to Sporothrix spp., showed high endoscopic scores (6–9) and the presence of fungal colonies. Among the 11 cases in which rhinoscopy suggested the presence of a polyp, histopathological examination confirmed neoplasia in three, reinforcing the importance of this complementary diagnostic procedure. The results reinforce the value of rhinoscopy in the evaluation of the nasal cavity; however, the isolated interpretation of endoscopic findings is insufficient to predict the diagnosis in cats with nasal disorders.
Rhinoscopy as a diagnostic tool - retrospective study of 52 cats
Keywords: Felinos; Endoscopia; Cavidades nasais; Rinite; Linfoma nasal; Felídeos